Interaksi Lintas Iman dan Pertumbuhan Rohani Kaum Muda Kristen: Sebuah Penelitian Fenomenologis dalam Lingkup Perkantas Jawa Timur - Pramono, Krisna Yogi; Pudjianto, Victor Kurniawan; Deswanto, Yusuf (Veritas : Jurnal Teologi dan Pelayanan, 2023)
Interfaith engagement has not been widely practiced in the evangelistic services of evangelical churches and institutions in Indonesia. This is unfortunate since intentional interfaith engagement among young Christians has a positive influence not only for the development of mission and evangelism, but also for the spiritual growth of the subject. This research is a qualitative study using the phenomenological paradigm. The data collection method was conducted by in-depth interviews through video-conferencing. The method of selecting informants was carried out by purposive sampling from Perkantas (Indonesian InterVarsity Ministry) of East Java, with the main criteria having been fostered in the Perkantas discipleship curriculum, and conducting interfaith engagements. The results showed that interfaith engagement is a valid expression of the praxis of evangelicalism; the dominant motive of interfaith interaction that appears is the proclamation of the gospel, and the impact of interfaith engagement is the appreciation of different faiths and the strengthening of the Christian faith.